Giant reed as energy crop for Southern Italy: An economic feasibility study. (May 2016) - Testa, Riccardo; Foderà, Mario; Di Trapani, Anna Maria; Tudisca, Salvatore; Sgroi, Filippo
Abstract: Among renewable sources giant reed has attracted a growing interest as energy crop especially in Southern Europe, thanks to its low agronomic input requirements. This paper aimed at evaluating the economic feasibility of introduction of giant reed plantation as energy crop in the Southern Italy. In particular, an economic and financial analysis was performed by comparing giant reed (both for woodchip and chopped forage production) with traditional crops (pluriannual and annual) that are currently cultivated in the same area, such as wine grape, melon and tomato. Results showed the highest profitability of giant reed respect to other crops with current market prices. In particular, giant reed destined to woodchip production denoted the highest annual gross margin with a value of 647.10 € ha −1, followed by giant reed for silage production (617.04 € ha −1 ), wine grape (477.52 € ha −1 ), melon (310.00 € ha −1 ) and tomato (280.00 € ha −1 ). However, it should be considered that, as the cultivation of energy crops subtracts inevitably surface to the agricultural land, it would be desirable that the giant reed does not conflict with agri-food production, but valorizes marginal and/or unproductive areas.